UPAYA PEMBINAAN DAN PENINGKATAN KUALITAS PRODUKSI INDUSTRI KECIL SERUNDENG KACANG NASI PADA KELOMPOK USAHA WANITA RIZKY DI KELURAHAN NEFONAEK KECAMATAN KOTA LAMA KUPANG (Universitas Wijayakusuma Purwokerto, 2023)
Serundeng kacang nasi is one of the rice bean processing attempts. Traditional processing and usage in the Rizky women's business group have failed to recognize the relevance of Good Production Management and marketing tactics in encouraging the expansion of the household industry, which can boost the family economy in Nefonaek Village. Another thing that needs to be done is to create added value products through one of the marketing functions that aims to foster the entrepreneurial interest of the community, particularly housewives, independently or in groups in Nefonaek Village Risky business groups, which has an impact on the fulfillment of Family Welfare. Counseling, training, and mentorship are the methods used in this service. The Rizky women's business group responded positively to the activities carried out, such as counseling and demonstration of the production processing process to the production packaging, so these activities will be continued with assistance from the women's business group, and it is expected that the women's business group will develop and produce quality and competitive products. Rizky Women's Business Group is also open to team input and suggestions, allowing this service activity to help the development of manufacturing firms.